PENGARUH NARSISME KLIEN, AUDIT FEE, INDEPENDENSI, SKEPTISME PROFESIONAL, DAN INTERLOCK AUDITOR EKSTERNAL TERHADAP AUDIT JUDGEMENT DALAM PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (STUDI KASUS PADA KAP DI MANADO) - Korompis, Claudia Wanda Melati; Latjandu, Lady Diana (Universitas Sam Ratulangi, 2017)
A material misstatement is the beginning of a fraud that can not be detected by an auditor and may have negative effects on the financial reporting process. The Internal factors related to the audit work environment in this research are audit fees, Independence, professional skepticism and Auditor Interlock. Sometimes, the amount of audit fee makes an auditor in a dilemma position on giving the opinion about the fairness of financial statements relating to the interests of many parties. The other factor which making a dilemma problem is Independence. Independence should be maintained by an auditor to provide a neutral assessment of the financial statements. Researchers also choose professional skepticism as things that need to be developed in order to reduce the adverse effects of fraudulent financial statement. The last Internal factor in this research is Auditor Interlock that may help auditor to get all disclosure that theyâ€™re needed. The unique external factor is client narcissism. Narcissism is known as a distorted personal characteristic that may obstruct an auditor's opinion statement according to the scope of the examination.The samples are all external auditors in KAP which operating in Manado area. Multiple linear regression analysis is an analysis thecnique that used in this research. Instrument in this research is questionnaire and processed using SPSS program.The results of this study indicate that the Audit fee and Independence have a significant effect on audit judgment. While Client Narsism, Professional Skepticism, and Interlock external auditors have no significant effect on audit judgment.Â Key Words: Narcissism, Fee, Independence, Skepticism, Interlock, Judgment